Low-Cost Glass Fiber-Reinforced Polymer Composite Wraps for Strengthening Deep Beams with and without Longitudinal Openings - Rodsin, Kittipoom; Ejaz, Ali; Hussain, Qudeer; Suthasupradit, Songsak; Parichatprecha, Rattapoohm; Shrestha, Kriti (My University, 2025)
This is a preliminary work on the application of low-cost glass fiber-reinforced polymer composites (Lo-Gs) wraps to enhance the structural response of shear-critical deep beams with and without openings. This study explores the performance of nine deep beams divided into three groups depending on the existence and number of longitudinal openings: solid section beams (Group 1), beams with one opening (Group 2), and beams with two openings (Group 3). Each group consisted of one unstrengthened beam and two beams strengthened with either one or two layers of Lo-Gs wraps. The results showed that Lo-Gs confinement effectively delayed failure in strengthened beams, while having minimal impact on the sudden failure behavior of unstrengthened specimens. Solid section beams exhibited peak load increases of 12.1% and 20.2% with one and two wraps, respectively. In contrast, beams with openings demonstrated higher but more variable strength gains. The presence of longitudinal openings diminished the effectiveness of the wraps in improving ultimate deflection and energy dissipation. While solid beams achieved up to a 130.1% increase in energy dissipation, beams with one and two openings showed lower gains of 63.4% and 57.0%, respectively. Existing design models, calibrated for synthetic FRPs, poorly predicted the behavior of beams with Lo-Gs wraps and neglected the effects of openings, emphasizing the need for further research and model development to address these limitations.
Keywords: Deep beams; Low-cost; Model evaluation; Shear; Strengthening